M2-like macrophages dictate clinically relevant immunosuppression in metastatic ovarian cancer - Vladimir Benes; Ladislav Pecen; Jelena Pistolic; Lorenzo Galluzzi; Iva Truxova; Radek Špíšek; Lenka Kasikova; Michal Hensler; Petr Skapa; Jan Laco; Ivan Praznovec; Tomas Brtnicky; et al. (Journal for ImmunoTherapy of Cancer)
Background The immunological microenvironment of primary high-grade serous carcinomas (HGSCs) has a major impact on disease outcome. Conversely, little is known on the microenvironment of metastatic HGSCs and its potential influence on patient survival. Here, we explore the clinical relevance of the immunological configuration of HGSC metastases.Methods RNA sequencing was employed on 24 paired primary tumor microenvironment (P-TME) and metastatic tumor microenvironment (M-TME) chemotherapy-naive HGSC samples. Immunohistochemistry was used to evaluate infiltration by CD8+ T cells, CD20+ B cells, DC-LAMP+ (lysosomal-associated membrane protein 3) dendritic cells (DCs), NKp46+ (natural killer) cells and CD68+CD163+ M2-like tumor-associated macrophages (TAMs), abundance of PD-1+ (programmed cell death 1), LAG-3+ (lymphocyte-activating gene 3) cells, and PD-L1 (programmed death ligand 1) expression in 80 samples. Flow cytometry was used for functional assessments on freshly resected HGSC samples.Results 1468 genes were differentially expressed in the P-TME versus M-TME of HGSCs, the latter displaying signatures of extracellular matrix remodeling and immune infiltration. M-TME infiltration by immune effector cells had little impact on patient survival. Accordingly, M-TME-infiltrating T cells were functionally impaired, but not upon checkpoint activation. Conversely, cytokine signaling in favor of M2-like TAMs activity appeared to underlie inhibited immunity in the M-TME and poor disease outcome.Conclusions Immunosuppressive M2-like TAM infiltrating metastatic sites limit clinically relevant immune responses against HGSCs.